Why Open Access? - López-López, Wilson (2015)
As mentioned in the previous editorial (López-López, 2015), Suber’s (2015) book is a significant contribution that we can use to clarify the limits and the scope of Open Access (OA), and it is also helpful in explaining confusions and inaccuracies that are widespread in our communities, which are not quite ready to face the accelerated changes that are being generated by the new dynamics of scientific output and communication (Gallegos, Berra, Benito, & López-López, 2014). Suber (2015) states that OA emerges in the context of motivating circumstances. These are: 1) The overwhelming increase in the fees of scientific journals, which has made access to knowledge more difficult. This has created more inequality and has deepened perverse paradoxes, such as the fact that poor countries produce knowledge that they cannot later access due to the inability to pay those exorbitant fees. This issue is critical for societies or libraries that have limited budgets to pay for access to databases, or countries looking to purchase relevant collections for their knowledge infrastructures, in association. The gaps created by high costs have an effect on the whole research community, and more so on those with worse economic restrictions. The resulting asymmetries make it harder to build collaboration networks. It is worth noting that the increase in those fees is often (much) higher than inflation indicators and the corresponding increases in institutional budgets. 2) The main publishing houses often sell journal packages (Big deals), consisting of journals of varying quality. This prevents negotiation of the journals that are strategically necessary for an institution, and cancelling subscriptions to low quality or low circulation journals is often punished with a premium. Even worse, publishers often subscribe confidentiality clauses with regards to prices and business conditions, which fosters a lack of transparency in the purchase of the aforementioned packages. 3) Price restrictions create access limitations, because the reproduction of contents is forbidden at every level – from basic training all the way to research proper. Besides, nowadays not even libraries own what they have paid for in the past. They can only “rent” the information, and migration of previous content is prevented, even if it has been purchased in the past. 4) An additional problem is that researchers transfer their publication rights to the publishing houses and these keep property rights over the contents. These contents must then be purchased by researchers, their institutions, libraries and even supporting entities, at a high cost. Most funding for research is provided by government/state institutions with public monies, and sometimes not even private universities are able to afford the disproportionate fees charged by some of these publishers. 5) These middlemen companies also create artificial scarcity by restricting access due to costs. As such, OA models can reduce those fees or at least they can try to keep them under inflation or real reasonable costs, including profit. But clearly, as said before, it should be possible to access research funded with public resources in the same way other public goods are accessed. For this reason, it is not reasonable to say that OA operates by “interfering with the free market”. 6) OA journals are competing for top quality authors and papers, and they are interested in getting this quality to reflect on different usages – they do not intend to compete or interfere with the paid journal market. Therefore, OA seeks that peer-review processes can guarantee the quality of its content. Many paid journals can actually increase their profit margins by increasing rejection rates. 7) A lack of knowledge of OA and even communication and circulation processes on the part of researchers, librarians and other actors in the production and circulation chains is often used by some of these companies to increase costs and even to engage in unethical practices. 8) All estimations of scientific output growth seem to show that the publishing business will continue to grow, with the corresponding impossibility of accessing contents under the current business model. It is therefore convenient and necessary that OA continues to develop and grow. 9) Since 2004, according to Suber (2015), Thomson Scientific identified a continued growth of OA journals in terms of impact, which is relevant since they are still young and must compete with journals with longer lifespans. Finally, we need to differentiate OA and peer-reviewed document repositories. Nowadays, repositories cover all sorts of content, and some which do not require peer review are called “dark repositories”. Gold OA, therefore, is Open Access with no regard for the business model, and Green OA is a self-archiving practice of placing one’s work into an OA repository. These terms enable us to differentiate the types of OA and their associated consequences – more such terms may be introduced in the future to clarify different models. In summary, Suber’s (2015) book will be a mandatory resource for those who are still committed to OA, because we understand the political and economical implications of inclusion and democratization of access to knowledge, especially in countries such as ours, where investment in science and education is scarce.